The Post-transplant Lymphoproliferative Disorders—Metagenomic Shotgun Microbial Sequencing (PTLD-MSMS) Study Methods and Protocol - Vikas R. Dharnidharka, MD, MPH; Kristine M. Wylie, PhD; Todd N. Wylie, BS; Marianna B. Ruzinova, MD, PhD; Charles W. Goss, PhD; Gregory A. Storch, MD; Neha Mehta-Shah, MD; Derek Byers, MD; Leslie Walther, RN; Lujain Jaza, MD; Hongjie Gu, MS; Mansi Agarwal, PhD, MPH; et al. (Transplantation Direct)
Post-transplant lymphoproliferative disorders (PTLDs) remain a feared complication of transplantation, with significant morbidity and mortality. The oncogenic Epstein-Barr virus (EBV) is a key pathogenic driver in 50%–80% of cases. Numerous prognostic indices, comprising multiple clinical, epidemiological and tumor characteristics, including EBV tumor positivity, do not consistently associate with worse patient survival, suggesting a potential role for EBV genome variants in determining outcome. However, the precision medicine tools for determining if a viral genome variant is pathogenic are very limited compared with human genome variants. Further, targeted studies have not implicated a specific viral etiological agent in EBV-negative PTLD. Using novel cutting-edge technologies, we are extracting viral nucleic acids from formalin-fixed, paraffin-embedded archived, or frozen PTLD tissues or plasma, to test for all vertebrate viruses simultaneously in an unbiased fashion, using metagenomic shotgun sequencing (MSS). We are collecting such samples from multiple transplant centers to address the following specific aims and close the following knowledge gaps: (1) Validate our novel observation that PTLD tissue positivity by MSS for anellovirus (and confirmed by PCR) serves as a biomarker for higher transplant recipient mortality after the diagnosis of PTLD; (2) determine the role of other oncogenic viruses in EBV-negative PTLD by unbiased MSS of multiple viral groupings, confirmed by other techniques; and (3) develop the necessary computational, algorithmic and software analytic tools required to determine association of EBV genome variants with worse presentations or outcomes in PTLD. Study completion will contribute to better patient care and may provide avenues for novel therapies.